NEW RECORD OF INDONESIAN PIGFISH, BODIANUS IZUENSIS ARAGA AND YOSHINO, 1975, AND B. MASUDAI ARAGA AND YOSHINO, 1975 (PERCIFORMES: LABRIDAE), FROM NORTH SULAWESI, INDONESIA - Peristiwady, Teguh (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2012)
One specimen of Bodianus izuensis Araga and Yoshino, 1975, and three specimens of B. masudai Araga and Yoshino, 1975, were obtained from fish markets in Bitung and Kema, Minahasa, North Sulawesi, Indonesia, between Marchâ??July 2009. The specimens were caught from depths of about 20â??30 m at coral reef ecosystem around Lembeh Island and Kema. This is the first record of these species in Indonesian waters. Morphological features, diagnostic characters, and distribution are discussed and illustrated, and color photographs of the species are presented.